PREMIERE study: reaching target blood pressure level – a success in coronary heart disease treatment - Yu. A. Karpov; S. A. Shalnova; A. D. Deev (Кардиоваскулярная терапия и профилактика)
Aim. To study ACE inhibitor effectiveness and safety in heart failure-free patients with arterial hypertension (AH) and stable coronary heart disease (CHD). Material and methods. Society of Cardiology of the Russian Federation initiated the National Program PREMIERE, focused on ACE inhibitor perindopril (2/4/8 mg/d) effectiveness, safety, blood pressure (BP) and clinical effects in AH and CHD patients. The number of participants achieving target BP levels, as well as therapy tolerability, was assessed. The study involved 199 doctors from 14 Russian cities; 1997 patients with AH and/or CHD, and associated risk factors (RF). Mean age of the patients was 57 years, mean follow-up duration – 6 months. In total, 1920 patients (96,1%) completed study protocol. Results. Perindopril treatment was associated with BP reduction; 86% of the participants reached target BP levels, <140/90 mm Hg, by the end of the study. Perindopril therapy was equally effective in men and women, regardless of age, CHD and diabetes mellitus. The weekly number of angina attacks and ischemic ECG sign rates significantly decreased. Comparing to pre-treatment 6 months, during 6-month therapy period, significantly less hospitalization cases were registered. Adverse events were observed in 165 patients (9,8%); in 44 participants (2,2%), the medication was withdrawn. Conclusion. PREMIERE study provided promising data on perindopril clinical effectiveness and tolerability (8 mg/d) in patients with AH, CHD, and RF. This treatment scheme could be recommended for primary healthcare settings.